Precision targeting of food biofilm-forming genes by microbial scissors: CRISPR-Cas as an effective modulator - Ghosh, Sreejita; Lahiri, Dibyajit; Nag, Moupriya; Sarkar, Tanmay; Pati, Siddhartha; Edinur, Hisham Atan; Kumar, Manoj; Mohd Zain, Muhammad R. A.; Ray, Rina Rani (Frontiers in Microbiology, 2022)
Abrupt emergence of antimicrobial resistant (AMR) bacterial strains has been recognized as one of the biggest public health threats affecting human race and food processing industry. One of the causes of emergence of AMR is due to the ability of the microorganisms to form biofilm as a defense strategy that restricts the penetration of antimicrobial agents into the bacterial cells. About 80% of the human diseases are caused by biofilm associated sessile microbes. Bacterial biofilm formation involves a cascade of genes regulated via the mechanism of quorum sensing (QS) and signaling pathways that control the production of extracellular polymeric matrix (EPS), responsible for the three- dimensional architecture of the biofilm. Another defense strategy utilized commonly by various bacteria includes clustered regularly interspaced short palindromic repeats interference (CRISPRi) system that prevents the bacterial cell from viral invasion. Since multigenic signaling pathways and controlling systems are involved in each and every step of biofilm formation, CRISPRi system can be adopted as an effective strategy to target the genomic system involving biofilm. Overall, this technology enables site-specific integration of genes into the host enabling the development of paratransgenic control strategies to interfere with pathogenic bacterial strains. CRISPRs- RNA-guided Cas9 endonuclease being a promising genome editing tool, can be effectively programmed to re-sensitize the bacteria by targeting AMR- encoding plasmid genes involved in biofilm formation and virulence to revert bacterial resistance to antibiotics. CRISPRi- facilitated silencing of genes encoding regulatory proteins associated with biofilm production are considered by researchers as a dependable approach for editing gene networks in various biofilm forming bacteria either by inactivating biofilm forming genes or by integrating genes corresponding to antibiotic resistance or fluorescent markers into the hosts genome for better analysis of its functions both in vitro and in vivo or by editing genes to stop the secretion of toxins as harmful metabolites in food industries thereby upgrading the human health status.